Intrapleural streptokinase in the management of empyema. Issue 9 (September 1994) - Taylor, R F; Rubens, M B; Pearson, M C; Barnes, N C
Abstract : BACKGROUND--Significant morbidity and mortality result from the ineffective evacuation of empyema. Failure of conventional first line treatment with closed intercostal tube drainage and antibiotic therapy may result in fibrin deposition and loculated empyema. Enzymatic debridement using intrapleural instillation of streptokinase is a non-invasive therapeutic option which may obviate the need for surgical intervention. METHODS--Eleven adults with multiloculated post-pneumonic empyemas who had failed to respond satisfactorily to intercostal tube drainage and antibiotic therapy were treated with intrapleural streptokinase between November 1992 and January 1994. A small catheter was inserted under ultrasound guidance into a loculation within the pleural space. Aliquots of 250, 000 units of streptokinase in 100 ml normal saline were instilled into the pleural cavity and the tube clamped for four hours. Response was assessed by clinical outcome, measurement of drain output after unclamping, and subsequent pleural ultrasound, chest radiography, or both. RESULTS--Streptokinase enhanced drainage in all patients. Complete resolution of the empyema with re-expansion of the underlying lung was effected in eight patients, all of whom remain well. Further resolution of minimal pleural thickening was shown on subsequent chest radiographs. Two patients with considerably thickened visceral pleura following empyema drainage underwent successful decortication. The other, with myocarditis and a pyopneumothorax, underwent surgery for non-resolution of the pneumothorax but died perioperatively from cardiac failure. The number of streptokinase instillations per patient ranged from two to six (median three), and the volume of empyema fluid drained per patient ranged from 100 ml to 4870 ml (median 900 ml). Streptokinase was well tolerated in all patients. CONCLUSIONS--Intrapleural streptokinase is an effective adjunct in the management of complicated empyema and may reduce the need for surgery.